2018
DOI: 10.31686/ijier.vol6.iss5.1031
|View full text |Cite
|
Sign up to set email alerts
|

Board Involvement on Earnings Per Share (EPS)

Abstract: This research aims to investigate the effect of board involvement on earnings per share. The current study uses the correlation and regression models to analyze publicly available data for a sample of 69 firms quoted in the Nigerian Stock Exchange for the fiscal year 2011. This indicates that the research made use of cross sectional data. Several diagnostic tests have been applied to justify the validity of the results. The empirical investigations reveal that director’ shareholdings, board size and board skil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The researcher of this work observed that from previous literatures, some researchers used written sentences to explain their conceptual frameworks (Nwokwu, Rathnasinghe, and Pradeep, 2019), while on the other hand, some researchers used diagram to represent their conceptual frameworks (Nwokwu, Atapattu, and Azeez, 2019;Nwokwu, Dharmadasa, and Rathnasinghe, 2018;Nwokwu, 2018).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…The researcher of this work observed that from previous literatures, some researchers used written sentences to explain their conceptual frameworks (Nwokwu, Rathnasinghe, and Pradeep, 2019), while on the other hand, some researchers used diagram to represent their conceptual frameworks (Nwokwu, Atapattu, and Azeez, 2019;Nwokwu, Dharmadasa, and Rathnasinghe, 2018;Nwokwu, 2018).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Financial condition refers to an assessment of the viability, stability, and profitability of a business. It is performed by preparing reports using ratios such as earnings per share (EPS), return on equity (ROE), price-earnings ratio (PE), return on asset (ROA), return on investment (ROI), and TOBIN'S Q that make use of financial information taken from accounting systems in financial statement parts to paint a more comprehensive picture of the firm's performance (Ashwath, 2007;Nwokwu et al, 2018;Nwokwu, 2018;Nwokwu et al, 2019).…”
Section: Factor To Be Considered In Implementing E-accounting In Gove...mentioning
confidence: 99%